Student Centered Approach to Teaching: What Does it Mean for the Stakeholders of a Community School in Karachi, Pakistan? - Qutoshi, Sadruddin Bahadur; Poudel, Tikaram (Journal of Education and Research, 2014)
Assuming the effectiveness of student-centered approach to teaching, this study explores the perceptions of purposefully selected seven students and teachers from a community school in Karachi about this pedagogical approach. Using interviews and observations of classroom practices as methodological tools, we concentrate on finding answers to the questions: How does student-centered approach to teaching used in community schools in Pakistan contribute to achieving quality education? How does this approach affect teaching and learning activities?  How does this approach facilitate teachers to overcome the problems of teaching and learning? The findings of this study identify that student-centered approach to teaching encourages students’ engagement in teaching-learning activities focusing on individual interaction to achieve common objectives. However, inadequate resources, small sized classrooms, and lack of expertise on the part of teachers were the challenges to the teaching learning activities in the community schools. These findings would be valuable to teaching and learning communities and educational policy makers as well.DOI: http://dx.doi.org/10.3126/jer.v4i1.9620 Journal of Education and Research, March 2014, Vol. 4, No. 1, pp. 19-33